The Effects of Intermittent Fasting on the Size and Number of Subcutaneus Adipocytes in Obese Mouse Models - Larasati, Veny; Rasyid, Riana Sari Puspita; Fertilita, Soilia; Suciati, Tri; Farhan, Muhammad (Folia Medica Indonesiana, 2024)
Highlights: 1. This study helps bridge the gap between systemic effects and tissue-level changes, providing a deeper understanding of how histological analysis can be used to explore the effects of intermittent fasting on adipocytes and body weight regulation. 2. This study contributes to obesity management through lifestyle modification, specifically intermittent fasting, by focusing on histological changes in adipose tissue. Abstract The accumulation of adipose tissue can have deleterious effects and lead to obesity. Intermittent fasting (IF), an approach that involves time-restricted eating, has gained popularity as an obesity treatment option because it enhances insulin sensitivity and promotes beneficial changes in glucose metabolism. This study used a time-restricted meal intake (TRM) approach to assess the effects of IF on the histological features of obese mouse models' subcutaneous inguinal adipose tissue. The investigation employed an in vivo experimental posttest-only control group design. Twenty male mice were divided into four groups: a normal control group, an obese control group, a TRM group with a high-fat diet (TRM-HF), and a TRM group with a standard diet (TRM-S). The TRM treatment was administered for fourteen days, with a fasting window from 4 p.m. to 8 a.m. The pre- and post-treatment weight analyses were conducted using the paired t-test for normally distributed data and the Wilcoxon test for non-normally distributed data (p<0.05). One-way analysis of variance (ANOVA) was employed for unpaired data on the post-treatment weight. Per field of view, there were an average of 120,500 cells (49,700–136,200) in the normal control group, 68,380±9,194 cells in the obese control group, 70,860±11,029 cells in the TRM-HF group, and 79,360±5,112 cells in the TRM-S group. The average cell sizes (Î¼m3) were 56,730.142±19,273.257 in the normal control group, 138,934.331±27,670.558 in the obese control group, 106,827.767±20,580.501 in the TRM-HF group, and 68,689.114±8,219.727 in the TRM-S group. The number of cells in each group did not differ significantly, but there were significant variations in cell size. The mice receiving TRM treatment did not exhibit substantial body weight changes, whereas the obese control group showed a significant body weight increase. In conclusion, TRM has an effect on cell size but does not affect the quantity of adipocytes in subcutaneous inguinal fat tissue.